2017
DOI: 10.1101/182071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photoperiodic control of the Arabidopsis proteome reveals a translational coincidence mechanism

Abstract: Plants respond to seasonal cues, such as the photoperiod, to adapt to current conditions and to prepare for environmental changes in the season to come. To assess photoperiodic responses at the protein level, we quantified the proteome of the model plant Arabidopsis thaliana by mass spectrometry across four 35 photoperiods. This revealed coordinated changes of abundance in proteins of photosynthesis, primary and secondary metabolism, including pigment biosynthesis, consistent with higher metabolic activity in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 83 publications
(188 reference statements)
1
24
0
Order By: Relevance
“…Significant protein phosphorylation changes were most frequently found in flowers (ED) and in rosettes (EN), whereas significant protein acetylation changes were most abundant in roots (ED) and in seedlings (EN) (Data S2; Table ). In contrast, few proteins in the proteomes from the same organs and seedlings had a Log2‐fold abundance change of >1.0 at the corresponding time points (Data S3), consistent with previous reports (Baerenfaller et al ., ; Graf et al ., ; Seaton et al ., ). To determine whether the observed changes in PTM levels resulted from changes in protein abundance we compared the quantified PTMome and total proteome.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Significant protein phosphorylation changes were most frequently found in flowers (ED) and in rosettes (EN), whereas significant protein acetylation changes were most abundant in roots (ED) and in seedlings (EN) (Data S2; Table ). In contrast, few proteins in the proteomes from the same organs and seedlings had a Log2‐fold abundance change of >1.0 at the corresponding time points (Data S3), consistent with previous reports (Baerenfaller et al ., ; Graf et al ., ; Seaton et al ., ). To determine whether the observed changes in PTM levels resulted from changes in protein abundance we compared the quantified PTMome and total proteome.…”
Section: Resultsmentioning
confidence: 97%
“…Our current understanding of circadian and light control is largely derived from genetic and transcriptomic studies, which have revealed the extent to which the expression of genes is regulated by the clock and the diurnal cycle (Endo et al ., ; Greenham and McClung, ; Nagel et al ., ; Nohales and Kay, ). More recent studies have shown that transcript and protein abundance may not always be correlated at the light–dark transitions during the diurnal cycle, indicating that transcriptional changes are not necessarily predictive for regulation at the protein level (Baerenfaller et al ., ; Graf et al ., ; Seaton et al ., ). Moreover, it is currently unknown if this lack of coincident transcript and protein‐level regulation also extends to proteins whose function is circadian clock‐ or light controlled by phosphorylation or acetylation, or both.…”
Section: Introductionmentioning
confidence: 97%
“…This makes it difficult to distinguish between direct and indirect effects when individual mutants are studied. Furthermore, although transcripts for proteins involved in photosynthesis, sucrose and starch metabolism and nitrogen metabolism often exhibit circadian rhythms (Farré & Weise, ; Harmer, ; Harmer et al, ; Harmer, Panda, & Kay, ; Michael et al, ; Smith et al, ; Usadel et al, ), these rarely lead to significant diel changes in the abundance of the encoded proteins (Baerenfaller et al, ; Dodd, Belbin, Frank, & Webb, ; Gibon, Bläsing, et al, ; Gibon et al, ; Seaton et al, ; Skeffington, Graf, Duxbury, Gruissem, & Smith, ; Stitt & Gibon, ). This underlines the need for studies of emergent metabolic responses that integrate circadian outputs, irrespective of whether the outputs act transcriptionally, posttranscriptionally, or posttranslationally.…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, the combined analysis of protein and mRNA abundance changes in diurnal regulation identified the synchronization of peaks in transcript levels and translation rates [43]. The authors suggest this result might be “translational coincidence” controlling the most dominant expression changes during the photoperiod.…”
Section: Understanding All Levels Of Gene Expression Regulationmentioning
confidence: 99%
“…While this example demonstrates how transcription and translation can oppose one another to achieve the desired outcome, examples of concordant regulation also exist. In Arabidopsis, the combined analysis of protein and mRNA abundance changes in diurnal regulation identified the synchronization of peaks in transcript levels and translation rates [43]. The authors suggest this result might be “translational coincidence” controlling the most dominant expression changes during the photoperiod.…”
Section: Understanding All Levels Of Gene Expression Regulationmentioning
confidence: 99%